Self-esteem moderates the impact of perceived social support on the life satisfaction of adults with autism spectrum disorder. (December 2022) - Tsermentseli, Stella
Background and aims: Although social resources and self-esteem are well-known predictors of subjective well-being in the general population, the relations among these factors have not yet been investigated in autism spectrum disorder (ASD). The present preliminary study sought to compare the levels of life satisfaction, self-esteem and perceived social support between adults with ASD and typically developing volunteers (TYP). It also examined whether self-esteem would moderate the effect of perceived social support on life satisfaction in adults with ASD. Methods: Fifty-seven adults with ASD without intellectual disability and 60 age-matched TYP in the United Kingdom (UK) completed self-reported measures of perceived social support, global self-esteem, and life satisfaction. Results: Results indicated that adults with ASD reported significantly lower levels of life satisfaction and self-esteem (but not social support) than TYP. Hierarchical regressions revealed that both social support and self-esteem were significant predictors of life satisfaction in adults with ASD. Self-esteem buffered the effect of perceived social support on life satisfaction. Conclusions: This study corroborated a growing body of evidence that suggests that adults with ASD report lower levels of self-esteem and life satisfaction than TYP. In addition, it reported for the first time that global self-esteem influences the association between social support and life satisfaction in adults with ASD. Implications: The present findings suggest that interventions aimed at enhancing self-esteem and cultivating social relationships could be important areas for intervention to improve the well-being of adults with ASD.